2016
DOI: 10.1016/j.ijpharm.2016.04.069
|View full text |Cite
|
Sign up to set email alerts
|

Topical delivery of hexamidine

Abstract: Hexamidine diisethionate (HEX D) has been used for its biocidal actions in topical preparations since the 1950s. Recent data also suggest that it plays a beneficial role in skin homeostasis. To date, the extent to which this compound penetrates the epidermis has not been reported nor how its topical delivery may be where there are minor differences in molecular structures. We also believe that they underline the ongoing necessity for fundamental studies on the interaction of topical excipients with the skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
4
15
0
Order By: Relevance
“…A new HPLC method was also developed for analysis of HEX H. With reference to topical delivery, HEX H has more favourable properties than HEX D, with a lower molecular weight and higher Log D value (pH 7.4). Consistent with these values, we have recently demonstrated >70% delivery of HEX H to porcine skin, in vitro, using a simple binary mixture of propylene glycol and propylene glycol monolaurate [12]. In contrast, the maximum amounts of HEX D that could be delivered were of the order of 30%.…”
Section: Hexamidine Dihydrochloridesupporting
confidence: 76%
See 1 more Smart Citation
“…A new HPLC method was also developed for analysis of HEX H. With reference to topical delivery, HEX H has more favourable properties than HEX D, with a lower molecular weight and higher Log D value (pH 7.4). Consistent with these values, we have recently demonstrated >70% delivery of HEX H to porcine skin, in vitro, using a simple binary mixture of propylene glycol and propylene glycol monolaurate [12]. In contrast, the maximum amounts of HEX D that could be delivered were of the order of 30%.…”
Section: Hexamidine Dihydrochloridesupporting
confidence: 76%
“…Recently, we outlined a rational formulation approach for effective targeting of HEX D and HEX H to the skin . Based on the solubility data reported in our earlier study , propylene glycol (PG), glycerol and PEG 200 were confirmed as suitable solvents.…”
Section: Topical Delivery Of Hexamidine Salts To the Skinmentioning
confidence: 99%
“…Although the cumulative amount of ANT that permeated was the lowest for PGML, the percentage permeation at 48 h was highest (13.1%) for this vehicle compared with the PG (0.6%) and TC (8.0%). The ability of PGML to act as a skin penetration enhancer has been reported previously (Hirata et al, 2013;Mohammed et al, 2014;Parisi et al, 2016). It has been suggested that the presence of unesterified lauric acid in PGML may contribute to increased membrane permeation.…”
Section: Accepted Manuscriptmentioning
confidence: 75%
“…If effective amounts of ANT penetrate the skin, the potential to progress the molecule as a topical chemotherapeutic agent may be explored further. As reported previously, vehicle selection was based on an assessment of solubility parameter values of various solvents and solubility determination (Parisi et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…As for PG, a linear correlation between signal intensity of DMI and the signal intensity of NIA was found (Mohammed et al, 2014). However, in a later study, DMI had no enhancing effect on the penetration of hexamidine diisethionate nor its dihydrochloride salt across pig skin in vitro (Parisi et al, 2016). In the present work, single solvent systems of DMI resulted in cumulative permeation of NIA of 9.8 ± 2.7 μg/cm 2 , corresponding to 6.1 ± 2.1% of the applied NIA.…”
Section: Permeation Studies Using Neat Solventsmentioning
confidence: 86%